PERSEPSI UKM TERHADAP APLIKASI AKUNTANSI BERBASIS ANDROID DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL DAN THEORY OF PLANNED BEHAVIOR - Embun Suryani; Sinta Almanika; Adi Septiawan (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
The purpose of this study was to determine the perceptions of Small and Medium Enterprises (SMEs) users and non-users of Android-based accounting applications as well as the benefits and feasibility of the application to be used as an SME accounting information system. This study uses phenomenological methods and analyzed descriptively. The data were analyzed using interactive analysis techniques which included data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the perception of SMEs using Android-based accounting applications provides a lot of positive responses, both from application users and non-users. The results of interviews with informants prove that android-based accounting applications can improve business performance and productivity, work faster, stored data is safer, and the accounting information produced is clearer, more complete, and accurate. Although most of the informants gave a positive response, a few informants were still comfortable using manual recording because it was considered easy and did not require complex recording. From the results of data analysis, the android-based accounting application has a feasibility level of 72% which indicates that this accounting application is very feasible to be used as a better financial recording of SMEs and meets accounting standards.Keywords:Keywords:SMEs perception, android-based accounting application, technology acceptance model, theory of planned behavior.